Tanggung Jawab Majikan Mengenai Hak Pembantu Rumah Tangga Berdasarkan Peraturan Menteri Ketenagakerjaan Repubik Indonesia Nomor 2 Tahun 2015 Tentang Perlindungan Pekerja Rumah Tangga Di Kota Pekanbaru - Muhammad Rizki Kurnia; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The low level of community education means that they can only work in jobs that suit theirabilities. Housework is one option that is quite easy for them to do. This is because householdchores are like the work they do everyday when they are at home. Legal protection forworkers/laborers is carried out so that the rights of workers/laborers are not violated by theirusers, bearing in mind that in a working relationship, the positions of the parties are not equal.Where workers/laborers are in a weak position both economically and socially, so that with thisweak position it is not uncommon for their rights to be violated. The existence of domestic workersin the workplace, without legal protection, without supervision from the authorities, without jobdescriptions, without regulations on working hours, without minimum wages, and without days off.This is an unfavorable condition for domestic workers. The purpose of writing this thesis is to findout the protection of housemaids, to find out the rights that are violated, and to find out whatresponsibilities are given by the users of housemaids regarding the rights that are violated.The type of research in this paper is sociological legal research, namely research on lawobserving what are the characteristics of a community's behavior in an area in an aspect of sociallife.From the research results, there are three main things that can be concluded. First, the rights thatare violated are: information about users of housemaids is not explained to housemaids, there isbad treatment from users of housemaids and their family members to housemaids, do not getwages in accordance with the work agreement, do not get food, do not get leave rights, and getadditional work outside of work as a domestic helper. Second, the responsibility given is to preventmistakes from happening, not to make the same mistakes, and to be responsible for the actions thathave been committed. Third, the protection of housemaids is divided into three, namely protectionof housemaids in law, protection provided by users of housemaids, and protection provided bydistributors of housemaids.Keywords: Legal Protection, Responsibility, Domestic Helpers